Processing and characterisation of calcium sulphoaluminate (CSA) eco-cements with tailored performances - García-Maté, Marta (Universidad de Málaga, Servicio de Publicaciones y Divulgación Científica, 2014)
Climate change mitigation usually involves the reduction of greenhouse gases emissions, such as carbon dioxide (CO2). Every tonne of Ordinary Portland Cement (OPC) produces about one tonne of CO2. Consequently, OPC accounts for 5-6% of anthropogenic CO2 emissions and for 4% of total global warming. Due to these environmental problems the industry of building materials is under increasing pressure to reduce the energy used in the production of OPC and the greenhouse gas emissions. Hence, there is a growing interest in developing alternatives to OPC, such as, calcium sulphoaluminate cements (CSA), that will release 0.25-0.40 tons of CO2 less than OPC per tonne of clinker, depending on their composition. Although CSA cements are very promising, their use is strongly limited in Europe. At the present state of European standard, CSA cements cannot be used in structural concrete according to the EN 206-1; only three formulations ,produced by Buzzi Unicemin Trino (Italy), obtained in 2013 a CE mark, also allowing the use for structural application. Hence, the general aim of this PhD Thesis is to better understand the behaviour of these eco-cement during their hydration. Moreover, I am a member of a working group which has a large experience in anhydrous cements and clinkers characterisation by X-Ray powder diffraction combined with Rietveld methodology, and in the processing of materials. So, I would like to highlight my contribution in the processing and characterisation of hydrated CSA pastes, including the quantification of ACn (Amorphous and Crystalline not-quantified) content through laboratory X-ray powder diffraction (LXRPD), and the measurement of mechanical properties of the corresponding mortars. Moreover, another objective was to establish a methodology to prepare, store and stop the hydration of cement pastes and mortars. Although anhydrous cements are mainly crystalline materials, they may contain a non-negligible amount of ACn; in addition part of the hydration products can be amorphous. This is the reason why the quantification of the ACn is an important issue. In previous studies, we used the internal standard methodology, measuring the sample in reflection geometry, to calculate the ACn content with quite accurate results. However, the addition of an internal standard may alter the cement hydration, dilute the phases in the pastes, and produce microabsorption problems. Hence, both external standard in reflection geometry and internal standard in transmission geometry methodologies have been compared. With that study, we can conclude that the ACn content in a mixture of powders can be calculated using both, internal and external standard, where the latter is of even greater utility in the study of hydration of cement pastes. That methodology has the inherent benefit of using common experimental requirements of LXRPD (knowing the diffractometer constant) and moreover, the sample is not altered/diluted. Moreover, the internal standard method is useful to corroborate the obtained values. However, the transmission approach is not very suitable for following ACn evolution in a process because it is experimentally tedious. Once we trust the methodology to control the hydration phases including ACn content, the effect of the following parameters on the hydration of CSA pastes and mortars was studied: gypsum content, sulfate source, water/cement (w/c) ratio, superplasticizer and the possible addition of fly ash (FA). The optimum w/c ratio must be high enough to have a high degree hydration of cement phases, and to provide workability, but in turn, it should be low enough to yield good mechanical strengths. The use of the optimum type and amount of additives improves the workability of cement pastes, allowing the use of lower w/c ratios and, consequently, higher compressive strength values. The optimised amount of gypsum to prepare CSA cements has been determined to be close to 25wt%. Therefore, we were able to correlate the phase assemblage of CSA pastes with compressive strength values of corresponding mortars. Another aim was the cost reduction of CSA cement and the study of the possible pozzolanic effect when the cement is partially replaced by FA. Although the hydration did not show enough evidences of pozzolanic effect even after 6 months of study, we found that the partial substitution produces: i) filling and ii) diluting effects. And we concluded that the partial substitution of cement (15wt% of FA) involves economic and environmental benefits. Moreover, the phase assemblage evolution is the same in the presence or not of FA, suggesting that durability is not compromised. Furthermore, the construction industry often requires cements with tailored properties. The knowledge and control of CSA hydration and properties of their mortars make possible the production of tailored cements and in the future, to comply all European standards. Through the use of different kinds of sulphate sources, w/c ratio and additives, the rheological behaviour and setting time of cement pastes have been controlled and modified while high compressive strength values were achieved. Each sulphate source (gypsum, bassanite or anhydrite) provides mortars with different setting times, as a consequence of their different rate of solubility. Hence, the use of different sulphate sources is a key point to control the rate of cement hydration. Bassanite solubility in water is very high thus, when added to cements/mortars it yields to short setting times (20min) that produces heterogeneous mortars with low mechanical strengths. However, the use of the optimum amount and type of additive, delays the setting time and allows the preparation of mortars with compressive strength values up to 80MPa at 7 days of hydration. Anhydrite dissolves slowly so, at 1 hydration-day, the amount of ettringite formed (~20wt%) is lower than that in gypsum pastes (~26wt%), producing mortars with lower compressive strengths (40.7 and 21.2MPa, respectively). However, after 3 hydration-days, similar ettringite contents are produced but mechanical strengths of anhydrite-pastes are slightly higher. This behaviour is mainly due to a higher plasticity of anhydrite-paste. Moreover, it must be noted that mortars with gypsum-w/c0.50 or anhydrite-w/c0.50 gave compressive strengths higher than OPC mortars at early ages. At this point, we are able to obtain tailored CSA eco-cements and mortars for diverse applications through the control of their hydration and also with the consequent economic and environmental benefits.
Keywords: Cemento - Tesis doctorales; Processing; Csa Eco-cements; Hydration; X-ray Diffraction; Compressive Strenght